First-principles calculations of the structural, electronic and optical properties of cubic BxGa1−xAs alloys - Guemou, M.; Bouhafs, B.; Abdiche, A.; Khenata, R.; Yarub, Al - Douri; S., Omran (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/